Anxiety, depression, and health-related quality of life in aging people living with HIV compared to diabetes patients and patients with minor health conditions: a longitudinal study. Issue 7 (9th August 2018) - Ronel, Joram; Dinkel, Andreas; Wolf, Eva; Marten-Mittag, Birgitt; Mueck, Birgit; Mayr, Christoph; Hoffmann, Christian; Karwat, Martin; Schewe, Knud; Baumgarten, Axel; Jaeger, Hans
Abstract: HIV infection has evolved from a fatal to a treatable condition, leading to an increase in the rate of elderly People Living with HIV (PLWH). However, little is known about the psychosocial burden of elderly PLWH. Thus, the aim of this longitudinal multi-center cohort study was to investigate whether elderly PLWH experience more anxiety and depression and reduced health related quality of life (HRQOL) compared to elderly patients with other chronic conditions. PLWH were compared to diabetes patients (DM) and patients with minor health conditions (MHC), e.g. patients with hypertension or allergic conditions. All patients were over 50 years old. Anxiety and depression (HADS) as well as HRQOL (SF-36) were assessed at baseline and after 12 months. 218 PLWH, 249 DM and 254 MHC were included. At baseline, the study groups did not differ in anxiety, depression, and physical HRQOL. However, PLWH indicated lower mental HRQOL than DM and MHC patients ( p = 0.001). We did not obtain any moderating effects showing a differential effect of patient characteristics on anxiety, depression, and HRQOL in the three patient groups. At follow-up, the level of anxiety, depression, and HRQOL did not change significantly. The prevalence of anxiety ranged between 27 and 35%, and that of depression between 17 and 28%. Thus, the results of our investigation tentatively suggest that the psychosocial adaptation to HIV among elderly PLWH resembles those of other chronic diseases. There may be some subtle impairments, though, as PLWH experienced lower mental HRQOL.